Sharks and minnows in a shoal of words: Measuring latent ideological positions of German economic research institutes based on text mining techniques - Sami Diaf; Jörg Döpke; Ulrich Fritsche; Ida Rockenbach (Hamburg University, Department Socioeconomics, 2020)
Using corpora of business cycle report sections dealing with monetary and fiscal policy issues from 1999 to 2017 and using methods of unsupervised text scaling (Slapin and Proksch, 2008; Lauderdale and Herzog, 2016), namely Wordfish and Wordshoal we scale the institutions' theoretical/ideological position over debates. The results are in line with the findings from descriptive textual analysis. For monetary policy, we observe a strong but short-lived consensus in debate-specific positions at the height of the financial crisis in 2008 and a larger polarization after 2008 compared to the sample period before. For the fiscal policy textual corpus, the polarization was similarly high before and after the crisis. For both policy areas, the institutions DIW Berlin and IfW Kiel define the outer bounds of the observed spectrum of latent ideological positions.
Keywords: E32; E52; E62; H3; C55; D7; P16; 330; Text Scaling Model; Word fish; Wordshoal; Computational Content Analysis; Hierarchical Factor Model; Bayesian Estimation; Political Economy; Ideology; Polarization; Public Policy; Monetary Policy; Fiscal Policy